Stevia water needs calculated from the crop coefficient - Daza Torres, Martha Constanza (2017)
This study aimed to determine the crop coefficient (Kc) curve for stevia (Stevia rebaudiana Bertoni) in Candelaria, Valle del Cauca, Colombia. The experiment was conducted during the first half of 2015. In a plot planted with stevia, were located three drainage lysimeters arranged randomly and a portable weather station to determine climatic variables necessary for calculating an evapotranspiration reference (ETo), using the Penman Monteith equation. Soil eld capacity moisture was determined and regular monitoring of both, soil moisture and drainage water depth were performed. Irrigation was applied using an exhaustion coefficient of 10% to bring it back to field capacity moisture. Statistical analyzes were performed and Kc was calculated from the ratio of crop evapotranspiration (ETc) to ETo, for each plant in phenological phase. With condidence of 95% Kc for stevia were: growth stage (54 days after transplantation, ddt) 0.86 ± 0.12, mature stage (55-72 ddt) 1.24 ± 0.10 and senescence stage (72-96 ddt) 0.85 ± 0.14. Water consumption of Stevia rebaudiana B., was 4753 m3/ha during its growing cycle of 96 days after transplantation.